(untitled) (The Gaze: Journal of Tourism and Hospitality, 2020)
The dimensions of travelling and tourism have become manifold in recent decades. People love to travel with various purposes. Religious tourism, yoga tourism, peace tourism and spiritual tourism are some dimensions. Lumbini can be a best destination for meditation tourism, which could be much rewarding for individual, social and national development. The travelers and stakeholders have yet to be aware of this aspect. In Buddhism, Lumbini is a best destination for meditation tour. Exploring the importance of travelling Lumbini for meditation is the main objective of this article. Tourists and pilgrims would benefit immensely if they understand the significance of meditation tourism to Lumbini, its philosophy and practice. This article aims to explore the spiritual significance of Lumbini and it will provide visions of a purposeful development and publicity that would shape Lumbini as a best destination for meditation tourism. The government and private sectors are interested to develop Lumbini as best tourist destination. People all over the world are attracted to visit Lumbini for different reasons. Most tourists are unaware of the core aspect of visiting Lumbini. People who visit Lumbini are unaware about meditation practice or involving in charity works. Meditation and compassion are the core aspects of Buddha’s teachings, which are neither realized nor practiced. There seems a vast gap between the actual philosophy of Buddhism and the attitude of most of the visitors. This research study attempts to reveal the significance of meditation tourism in Lumbini.